TANTANGAN DAN PELUANG PERPUSTAKAAN DAN ARSIP KABUPATEN KLATEN DALAM MENDUKUNG PELESTARIAN BUDAYA DAERAH DI TENGAH PERKEMBANGAN TEKNOLOGI - Ashfi Fauziani Ilahiya; Astrid Gisca Anggraini; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
The development of information technology presents both challenges and opportunities for libraries and archival institutions in preserving local culture. This study aims to analyze the efforts and challenges faced by the Library and Archives Office of Klaten Regency in supporting the preservation of regional culture amid the rapid pace of digitalization. A qualitative descriptive method was employed, with data collected through interviews, observations, and document analysis. The findings indicate that digitalization offers several opportunities, including service innovation, increased collaboration, expanded access to information, and enhanced public participation. However, several challenges remain, such as limited human resources, low levels of public education, suboptimal development of local libraries, and a lack of initiative from various stakeholders. The strategies implemented show potential in strengthening the role of libraries and archival institutions as centers for both documentation and cultural education. By optimizing the use of technology, local cultural preservation can be carried out in an innovative and sustainable manner, thereby engaging younger generations to learn about and appreciate their regional heritage.